Pemanfaatan Pemasaran Melalui Media Sosial Terhadap UMKM di Kota Serang - Maria, Vera; Hidayatullah, Ahmad Fauzan; Tunning Putri , Ussy Emmelly Devy; Mursidah, Nadia Nurul; Ramdhany, Levina Putri; Sabilah, Rana; Syauqi, Fakhriza Aqsyal (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2024)
Social media has a big role in today's society, including in developing MSME marketing. The purpose of this research is to find out how many MSMEs in Serang City use digital platforms as a marketing strategy. Researchers used a qualitative descriptive literature study approach, by analyzing existing literature. The research findings show that Facebook, Instagram, YouTube, WhatsApp Business, and TikTok are the most popular social media platforms. The majority of MSMEs use social media because it can increase brand awareness more easily and affordably, provide feedback on products and marketing initiatives, and create networks with suppliers, competitors and customers.